A new species of Pseudophryne (Anura: Myobatrachidae) from the central Australian ranges - Donnellan, S. C.; Mahony, M. J.; Bertozzi, T. (Zootaxa, 2012)
The myobatrachid frog genus Pseudophryne is highly variable in color pattern in eastern Australia where many species are distinguished by distinctive dorsal patterns. In contrast Pseudophryne from the western half of the continent are morphologically conservative. Two nominal species are widespread in south-western Australia and north-western South Australia, with one, P. occidentalis, being found in semi-arid and arid regions. Using mitochondrial DNA and morphological characters we establish that populations in the ranges of north-western South Australia assigned to P. occidentalis are a separate species. The new species comprises one of four major lineages of Pseudophryne while P. occidentalis falls within another lineage confined to south-western Australia.